AN ANALYSIS OF SPEECH ACTS IN BEAUTY PRODUCT ADVERTISEMENTS POSTER - Sesilia, Kadek Icha; Ediwan, I Nyoman Tri; Agung, I Gusti Ayu Mahatma (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The phenomenon of selling a product with a catchy headline but still with a subtle selling method is often found in today's world. The problem discussed in this article is that advertisements are sometimes misinterpreted by readers. The purpose of this article is to find out what classification of speech acts is used in some beauty product advertisements posters on the internet. Qualitative descriptive analysis and observational methods were used in this article. It is found that some advertisements have a tendency to fall into the classification of assertive and directive speech acts.